Finite Element Modeling for Development and Optimization of a Bone Plate for Mandibular Fracture in Dogs - Freitas, Elisangela P. [UNESP]; Rahal, Sheila Canevese [UNESP]; Gioso, Marco Antonio; Vulcano, Luiz Carlos [UNESP]; Shimano, Antonio Carlos; Lopes da Silva, Jorge Vicente; Noritomi, Pedro Y.; El Warrak, Alexander O. (Nichepubs, 2010)
This study aimed to develop a plate to treat fractures of the mandibular body in dogs and to validate the project using finite elements and biomechanical essays. Mandible prototypes were produced with 10 oblique ventrorostral fractures (favorable) and 10 oblique ventrocaudal fractures (unfavorable). Three groups were established for each fracture type. Osteosynthesis with a pure titanium plate of double-arch geometry and blocked monocortical screws offree angulanon were used. The mechanical resistance of the prototype with unfavorable fracture was lower than that of the fcworable fracture. In both fractures, the deflection increased and the relative stiffness decreased proportionally to the diminishing screw number The finite element analysis validated this plate study, since the maximum tension concentration observed on the plate was lower than the resistance limit tension admitted by the titanium. In conclusion, the double-arch geometry plate fixed with blocked monocortical screws has sufficient resistance to stabilize oblique,fractures, without compromising mandibular dental or neurovascular structures. J Vet Dent 24 (7); 212 - 221, 2010